Strategi Pengembangan Pusat Pendidikan Lingkungan Hidup (Pplh) Seloliman Di Kabupaten Mojokerto, Jawa Timur - Heni Habibah; Lina Karlinasari; Siti Badriyah Rushayati (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2022)
The Environmental Education Center (PPLH) Seloliman is a place for environmental education for students, teachers and the public who can learn and interact directly with the actual state of nature. The development of PPLH Seloliman has a very important role in the success of environmental education. This study aims are to analyze internal and external factors for the existence of PPLH Seloliman, analyzing the strategic position of PPLH Seloliman development, and developing alternative strategies for developing PPLH Seloliman. Survey methods and analysis of Strength-Weakness-Opportunity-Threats (SWOT) were carried out in this study. The result showed there are seven strength variables and three weakness variables on internal factors, six opportunity variables and three threat variables on external factors. The strategic position of PPLH is in quadrant I, an aggressive management strategy by taking advantage of strengths and opportunities. Alternative development strategies for PPLH Seloliman that are generally identified are collaboration with relevant ministries (Ministry of Tourism and Creative Economy, Education, Culture, Research and Technology, and Ministry of Environment and Forestry Ministry), private institutions (tourism travel service bureaus and mass media), and academics in terms of adding media innovations to support environmental education at PPLH Seloliman.